Pelatihan Pembuatan Blog/Website Pribadi Gratis Untuk Siswa di Sekolah SMK Bintang Nusantara (Binusa) Tangerang Selatan - Artaningsih, Eka Yuni Titik; Purnomo, Bram; Muhajir , Abdullah (Praxis: Jurnal Pengabdian Kepada Masyarakat, 2023)
In the current era of technology, the source of information that is in great demand by the public is the internet. This computer network can provide complete and actual information that covers almost all aspects of life, one of which is in the aspect of education. Many students use the internet to simply seek information about science as a learning solution outside of school. Blogs/websites are one of the targets of students in finding references to their knowledge. At the Bintang Nusantara Vocational School located in the South Tangerang area, it is a vocational school that has programs majoring in Multimedia (MM) and Network and Computer Engineering (TKJ). To develop and broaden the knowledge of Bintang Nusantara Vocational High School students, in this PKM activity this time we want to provide knowledge and training on creating personal blogs/websites for free with the aim that students can not only enjoy ready-made blogs/websites but they can find out how to make it from scratch. In addition, creating a blog can be useful for self-improvement both in increasing knowledge and improving writing skills and the ability to understand technology for students.